Interventional treatment of pain in refractory angina. A review - Dobias, Milos; Michalek, Pavel; Neuzil, Petr; Stritesky, Martin; Johnston, Paul (Biomedical papers, 2014)
Background: Refractory angina is characterized by repeated attacks of chest pain in patients on maximal anti-anginal pharmacotherapy, with a professional conscensus that further surgical or radiological revascularization would be futile. Refractory angina is a serious but relatively uncommon health problem, with a reported incidence of approximately 30 patients per million people/year. In this condition simply treating the associated pain alone is important as this can improve exercise tolerance and quality of life.Methods: An extensive literature search using five different medical databases was performed and from this, eighty-three papers were considered appropriate to include within this review.Results and Conclusion: Available literature highlights several methods of interventional pain treatment, including spinal cord stimulation and video-assisted upper thoracic sympathectomy which can provide good analgesia whilst improving physical activities and quality of life. The positive effect of spinal cord stimulation on the intensity of pain and quality of life has been confirmed in nine randomized controlled trials. Other potential treatment methods include stellate ganglion blocks, insertion of thoracic epidural or spinal catheters and transcutaneous electrical nerve stimulation. These approaches however appear more useful for diagnostic purposes and perhaps as short-term treatment measures.
Keywords: refractory angina; spinal cord stimulation; thoracic sympathectomy; stellate ganglion